The Effect of Sr composition on the microstructure and mechanical properties of Al-Si-Zn filler for the brazing of AA6061. (1st February 2022) - Wang, Guangyu; Ma, Rui; Wan, Mingpan; Zhao, Fei
Abstract: The microstructure and properties of Al-Si-Zn-Sr filler metals and brazed 6061-T6 aluminum alloy after heat treatment were studied, and the adsorption energy of Sr element on Si (111) surface was calculated. After Sr was added to Al-6Si-40Zn filler metal, its melting range remained unchanged, and the spreading wettability was improved. The microstructure mainly includes α -Al solid solution, fibrous Si, and η -Zn solid solution. Generally speaking, increasing Sr content could improve the average microhardness of brazed joints. The shear strength of the brazed joint containing Al-6Si-40Zn-0.8Sr filler metal was 134.23 MPa, which was 39.3% higher than that of the brazed joint without Sr The calculation results of adsorption energy showed that the surface of Si (111) mainly adsorbed Sr at the vacancy, which changed the growth mode of Si.